Researching Community Psychology: Issues of Theory and Methods.
DOI: 10.1037/10073-013
|View full text |Cite
|
Sign up to set email alerts
|

Implementing research: Putting our values to work.

Abstract: It is the participatory spirit of the research enterprise that cames it forward toward significant discovery, useful theory, and approximate application. (D. Klein, 1985) 171

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 0 publications
2
61
0
Order By: Relevance
“…We need to see who we are ourselves, our anxieties, our precepts, our premises, so we are aware of how our conclusions can reflect more of us than context'' (personal conversation, June 9, 2007). Reflection on our ''cultural experiences'' (Bond and Harrell 2006), including our identities, competencies, histories, and interests, in relation to those with whom we work and collaborate has the potential to foster relationships, mutual openness and willingness for challenge, growth and development (Bond and Harrell 2006;Heller 1989;Kelly 1970Kelly , 1971Nelson et al 2000;Serrano-García 1990;Prilleltensky et al 1997;Trickett and Schmid 1993). Developing an eco identity challenges the community psychologist to be open to transformation, new insight, and ''rich points'' (Agar 1996) that emerge during immersion in a setting that challenge prior assumptions.…”
Section: The Spirit Of Ecological Inquirymentioning
confidence: 96%
See 1 more Smart Citation
“…We need to see who we are ourselves, our anxieties, our precepts, our premises, so we are aware of how our conclusions can reflect more of us than context'' (personal conversation, June 9, 2007). Reflection on our ''cultural experiences'' (Bond and Harrell 2006), including our identities, competencies, histories, and interests, in relation to those with whom we work and collaborate has the potential to foster relationships, mutual openness and willingness for challenge, growth and development (Bond and Harrell 2006;Heller 1989;Kelly 1970Kelly , 1971Nelson et al 2000;Serrano-García 1990;Prilleltensky et al 1997;Trickett and Schmid 1993). Developing an eco identity challenges the community psychologist to be open to transformation, new insight, and ''rich points'' (Agar 1996) that emerge during immersion in a setting that challenge prior assumptions.…”
Section: The Spirit Of Ecological Inquirymentioning
confidence: 96%
“…Such inquiry is theorized to improve internal and ecological validity (Kelly et al 2000;Kingry-Westergaard and Kelly 1990;Mohatt 1989;Serrano-García 1990;Trickett 1996Trickett , 1997Trickett et al 1985;Walsh 1987), interpretation of data (Mohatt 1989;Trickett 1997), dissemination of results (Chavis et al 1983;Mohatt 1989), utility of community research (Chavis et al 1983;Kelly and Hess 1986;Trickett et al 1985), and community transformation and development through selfhelp and advocacy (Bracht and Tsouros 1990;Hawe 1994;Kelly 1986a;Trickett et al 1985).…”
Section: Introductionmentioning
confidence: 96%
“…Research partners may find themselves having to ask Bat what point do the needs of the many outweigh those of the few?F inally, ethical issues may arise in relation to disseminating or releasing sensitive or potentially unflattering data. 40,42,44,45,48,51 Academic partners may feel an imperative to publish and to Bstay true^to the Bobjective^nature of the data. Community members, however, may fear that unflattering data may (further) stigmatize their communities.…”
Section: But Is Cbpr Inherently Bethical^?mentioning
confidence: 99%
“…21,49,50 Sometimes it may be important to obtain consent at a Bcommunity^level from respected or elected community leaders. 46,48,51 This may cause conflict when community leaders and members disagree on the importance of a research issue.…”
Section: But Is Cbpr Inherently Bethical^?mentioning
confidence: 99%
“…In some instances, however, individuals who share an ethnic identification with the community may have a more difficult time within lower income communities if the researcher is perceived as being from a different social class or is seen as someone who has "sold out" to the mainstream establishment. Community residents and CBO staff often have experienced forms of oppression that make them leery of anyone coming from outside of the organization (Perkins & Wandersman, 1990;Serrano-Garcia, 1990). Thus, we have found that the most central concern is a shared commitment to improving the conditions for the people who live in their community, regardless of whether or not there is an exact cultural or ethnic match between the team and the community.…”
Section: Respecting Human Diversitymentioning
confidence: 98%